Redox biology enabled screening of drought resilient genotypes of edible Amaranths of Gangetic plain of West Bengal and their implication in health benefits - Bhattacharjee, Soumen; Sen, Debasmita (South African journal of botany, 2025)
•Redox biology of Amaranths influence Drought resilience property.•Drought-induced redox metabolic interactome studies revealed genotype impact.•Redox biology influence on hormonal profile, root phenotypes and stress tolerance.•Tandem action of Ascorbate-glutathione and phenylpropanoid pathway for resilience.•Drought tolerant amaranths with rich bioactive polyphenolic antioxidants. Though information on the wide adaptability and scattered evidences of stress resistance attributes of potential alternate crop Amaranth are available in the literature, but no systematic study has been made to unfold their genotype-based drought resilience property and hence was the subject of present investigation. The present work explored the impact of drought stress during pre-flowering stage on redox biology, hormonal profile, important morpho-phenotypic traits, and accumulation of nutritionally important bioactive polyphenolic compounds for screening drought-tolerant amaranths of Gangetic plain of West Bengal. Drought induced redox biology of experimental Amaranths were studied in terms of redox interactome and sensitive biomarkers of oxidative stress [assessed in terms of kinetics of generation of total ROS, accumulation of O2·-, H2O2, oxidative degradation products of membrane proteins and lipids (hydroperoxide, TBARS, conjugated diene, free carbonyl content), efficacy of Halliwell-Asada Pathway, bioactive polyphenolic compounds derived from phenylpropanoid pathway]. Further, the impact of drought induced redox metabolic shift on hormonal profile (IAA, GA, JA, ABA) was studied along with root morpho phenotyping (suberin layer lamellae and branching pattern). The result in general showed genotype – specific response of amaranths imposed to drought stress during pre-flowering stage. Work noticed complementation of Halliwell–Asada pathway with phenylpropanoids pathway (assessed in terms of accumulation of bioactive flavonoids, flavones, favonones, flavonol, phenolic acids) for strengthening of redox-tuning ability, essential for drought resilience in Amaranth germplasms. Drought stress induced differential redox metabolic shift exhibited strong impact on hormonal profile (particularly ABA) and root morpho-phenotypes including root suberization associated with tolerance. Hierarchical cluster analysis employing sensitive redox biomarkers and phenotypes revealed A. hypochondriacs L. as drought resistant and A. hybridus L. a drought-sensitive germplasms among the seven available cultivatable germplasms of amaranths of Indo Gangetic plains of West Bengal. Taken as a whole, the work elucidated genotype impact of redox regulation of vegetable Amaranths in relation to their drought resilience and phytonutrient promise, which may be explored for screening drought-tolerant Amaranths and other millets necessary for future breeding programs for crop diversification and improvement.